PENGARUH KOMITMEN PROFESIONAL AFFECTIVE, KOMITMEN PROFESIONAL CONTINUANCE, KOMITMEN PROFESIONAL NORMATIVE, DAN KOMITMEN ORGANISASI TERHADAP PERILAKU DISFUNGSIONAL AUDITOR (Studi Empiris Pada Kantor Akuntan Publik di Medan) - Widya Ayu Tamara; Zulbahridar Zulbahridar; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study examine influence effect ofaffective professional commitment, continuance professional commitment, normayive professional commitment, andorganizational commitment toward dysfunctional audit behavior. Respondents in this study are auditors who worked public accounting firm in Medan.The number of auditor that were visited in tihis study were 95 auditors from 19 public accounting firms.. The method of determining the sample is by using purposive sampling method, while the data processing method used by reseacher are the multiple analysis and use SPSS version 20.0 as the software for processing the data. The result shows that the affective professional commitment give a significant influence dysfunctional audit behavior.Continuance professional commitment give a significant influence in dysfunctional audit behavior. Normative professional commitment give a significant influence in dysfunctional audit behavior. Organizational commitment give a significant influence in dysfunctional audit behavior.Keywords : affective professional commitment, continuance continuance professional commitment, normative professional commitment, organizational commitment, audit behavior